1991
DOI: 10.1016/0014-5793(91)80468-i
|View full text |Cite
|
Sign up to set email alerts
|

A homologue of dystrophin is expressed at the neuromuscular junctions of normal individuals and DMD patients, and of normal and mdx mice Immunological evidence

Abstract: Palyelanal (DMD) patients and rndjc mice through mutations which disrupt the reading frame of the transcript preventing dystrophin expression in the corresponding skeletal muscles [g-14]. I-Iigh concentrations of dystrophin (or a dyscrophin-like protein) have been observed at the neuromuscular junctions (NMJ) in normal rats, rabbits or mice as well as in the electric organ of Torpedo marmwata recently reported a positive immunofluorescence response at the NMJ of DMD patients and rndx mice, using antibodies r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 27 publications
3
38
0
Order By: Relevance
“…As far as the mdx genotype is concerned, a slight but significant increase in utrophin content was found in both sedentary and exercised DIA muscles versus WT groups. This is in line with earlier observations 40,41 and may indicate a compensatory mechanism activated in surviving muscle fibers to withstand both pathology and exercise protocol. Interestingly, the CsA treatment did not increase nor decrease the utrophin content in a significant manner with respect to the mdx groups.…”
Section: Effect Of Csa Treatment On Fibrosis Utrophin Expression Ansupporting
confidence: 93%
“…As far as the mdx genotype is concerned, a slight but significant increase in utrophin content was found in both sedentary and exercised DIA muscles versus WT groups. This is in line with earlier observations 40,41 and may indicate a compensatory mechanism activated in surviving muscle fibers to withstand both pathology and exercise protocol. Interestingly, the CsA treatment did not increase nor decrease the utrophin content in a significant manner with respect to the mdx groups.…”
Section: Effect Of Csa Treatment On Fibrosis Utrophin Expression Ansupporting
confidence: 93%
“…Particularly strong conservation of this region between utrophin and dystrophin, suggests that utrophin may take part in similar interactions. Immunohistology using sensitive monoclonal antibodies has localised utrophin at the neuromuscular junction (NMJ) in normal skeletal muscle but a t the NMJ and non-junctional sarcolemma in small muscles and heart of mdx mice and thigh muscle of Duchenne patients, (Ohlendieck et al, 1991;Khurana et al, 1991;Pons et al, 1991;thi Man Nguyen et al, 1991). Utrophin has also been shown to associate with the glycoprotein fraction which normally complexes with dystrophin in the mdx mouse (Matsumura et al, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Immunoblot analysis of skeletal muscle homogenates has shown that the protein product of this gene, dystrophin-related protein (DRP or utrophin), is similar in size to dystrophin [14~ 21]. In adult skeletal muscle, DRP is localized to the neuromuscular junction [15,[17][18][19][20]22], where it is associated with a large oligomeric complex of sarcolemmal glycoproteins which are identical with or antigenically similar to the dystrophin-associated proteins [22] possibility that the upregulation of DRP could have compensatory effects for dystrophin deficiency was raised [18][19][20]22,23], based on the findings that DRP is overexpressed and the dystrophin/DRP-associated proteins are preserved in the small-caliber skeletal and cardiac muscles of mdx mice which show minimal pathological changes [22].…”
Section: Introductionmentioning
confidence: 99%